Designing and testing an MI-based interactive web platform: Enhancing biological concept understanding and multiple intelligence development - Risya Pramana Situmorang; Martha Eka Latelay; Dujun Durinam Selan (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Conventional biology teaching methods often do not address the diversity of learning styles and students' multiple intelligences. The study aims to investigates the effectiveness of an interactive web platform, grounded in the theory of multiple intelligences, in improving students' understanding of biological concepts and multiple intelligences. Quasi-experimental using 50 students were assigned to Quasi-experimental using 50 students were assigned to (25 experimental, 25 control). Data were collected through academic achievement pretests and post-tests, as well as multiple intelligences questionnaires, and analyzed using t-tests and Cohen's d effect size. The experimental group demonstrated significant academic improvement with a large effect size (d = 0.86; p < 0.001). Analysis of multiple intelligences indicated varied development patterns, with the largest within-group effect sizes observed in bodily-kinesthetic (d = 2.29), visual-spatial (d = 2.18), and interpersonal intelligence (d = 1.71). Between-group analysis showed the most excellent effectiveness for verbal-linguistic (d = 0.59), interpersonal (d = 0.53), and logical-mathematical intelligence (d = 0.53). The results found that an interactive web platform based on multiple intelligences effectively improved academic achievement and supported the development of students' multiple intelligences, particularly in the kinesthetics, spatial, and social domains. Therefore, this research supports the principle of integrating Multiple Intelligences principles into digital learning design as an alternative strategy for more inclusive and holistic science education.